Pengaruh Penggunaan Media Papan Mari Mengenal Huruf Kapital terhadap Hasil Belajar Peserta Didik Kelas V Mata Pelajaran Bahasa Indonesia pada Materi Huruf Kapital di Minu Waru I - Rekha Widiawati; Citra Oktavina Eka Lidyawati; She Fira Azka Arifin (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study aims to determine the effect of using the "Let's Get to Know Capital Letters" Board media on the learning outcomes of grade V MINU Waru I students in the Indonesian Language subject. This study uses a quantitative approach with a one-group pretest-posttest design on 28 students. The instrument used was a written test given before and after the treatment. The pretest results showed an average value of 64.5, while the posttest increased to 83.2. Statistical tests showed significant results with a p value = 0.000 (<0.05), which indicates that there is a meaningful difference between before and after using the media. This board media is designed to facilitate students' visual and interactive understanding of capital letter material. The results of the study indicate that this media is effective in improving student learning outcomes. The use of concrete and fun media has been proven to increase student involvement and motivation in the Indonesian Language learning process. Thus, the application of innovative media like this can be an effective strategy to improve the quality of education in elementary schools.